THE EFFECTIVENESS OF ONLINE SOCIAL MARKETING COMMUNICATION ON PROMOTING OF USING GREEN SPACES IN BANGKOK THROUGH STAGES OF CHANGE MODEL - Khamdaeng , Sireeporn; Vantamay, Nottakrit (Journal of MCU Nakhondhat, 2023)
The purpose of this research was to study of The Effectiveness of Online Social Marketing Communication on Promoting of Using Green Spaces in Bangkok Through Stages of Change Model. This research used 4 Stages Contemplate, Preparation, Action and Maintenance. The research use Quantitative Research and use Survey Research to collect information. The samples of 400 persons from Facebook Fan Page Green Spaces in Bangkok. The statistics used in the data analysis were frequency, percentage, mean standard deviation and Multiple Regression Analysis (MRA). The results of the research found that 1) The samples general information are female, aged 20 – 30 years old, working as employees, have an average monthly income of less than 15,000 baht. 2) The samples exposure online social marketing communication in all tools was on middle level and the samples exposure in Facebook the most on moderate level. The samples have Stages of Change Model in Contemplate, Preparation, Action and Maintenance on moderate level and when considering the effectiveness of online social marketing communication on promoting it was found that TikTok (β = .250), Facebook (β = .240) and Twitter (β = .223) influence of Contemplate, Instagram (β = .251) influence of Preparation, Facebook (β = .312) influence of Action, Facebook (β = .245) and Instagram (β = .179) influence of Maintenance. The results of this research can be useful for planning online social marketing communication on promoting of using green spaces in Bangkok most effectively and recompense user satisfaction as possible.